2021
DOI: 10.5604/01.3001.0015.5609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and relative humidity on the milk production of dairy cows

Abstract: The aim of this study was to evaluate the influence of environmental housing conditions on the milk yield of dairy cows. Measurements were taken in the summer period from June to September 2020 and in the winter period during January 2021 on a large-capacity farm of Holstein Friesian cattle. Cows were housed in free stall barn with the lying boxes and selected during the second or third lactations, in the summer period from the 51st day to the 135th day and in the winter period from the 64th day to the 120th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…For milk processors, it is extremely important that purchased raw material is characterized by the qualitative and quantitative composition that remains as uniform as possible throughout a year. Similar observations were made by Imrich et al (2021), who noted a negative correlation between THI and the milk yield (r=-0.64) and the fat content (r=-0.24).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For milk processors, it is extremely important that purchased raw material is characterized by the qualitative and quantitative composition that remains as uniform as possible throughout a year. Similar observations were made by Imrich et al (2021), who noted a negative correlation between THI and the milk yield (r=-0.64) and the fat content (r=-0.24).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent results were obtained in an experiment conducted on the Holstein-Friesian cows, in which it was noted that in the summer, an increase in THI by one unit resulted in the milk yield decrease by 0.11 kg (Imrich et al, 2021). The obtained results were confirmed by studies of Ravagnolo et al (2000), who analysed, among others, relations between overall milk yield and heat tolerance in Holstein-Friesian cattle.…”
Section: Discussionsupporting
confidence: 80%
“…The report by Imrich et al [48] on the testing the effects of temperature and RH on FH cows in Slovakia revealed that in the summer season (temperature 23°C; RH 66.89%; THI 70.43%) and winter season (temperature 7°C; RH 78.86%; THI 46.16), considerable effects were observed in the following parameters (summer vs. winter): milk yield (49.55 vs. 58.77 kg/head/day); milk fat content (3.71% vs. 3.76%); milk protein (3.44% vs. 3.57%); lactose (5.06% vs. 5.2%); and somatic cells (144,797 vs. 131,500 count/mL). It was concluded that RH and temperature during the summer season in Slovakia have a negative impact on the milk production and composition of cow's milk.…”
Section: Impact Of Heat Stress Factors On Fh Dairy Cattle In Indonesi...mentioning
confidence: 93%
“…Stress is a reflexive reaction that results in the animal's inability to adapt to its environment, which leads to many negative effects from stresses facing the animal, causing a decrease in its production, leading to death [1] and heat stress is the most harmful as it affects animal production [2,3] .which is a set of environmental factors represented in temperature, relative humidity, air movement and solar radiation that cause the effective temperature of the environment to be higher than the comfort zone of IOP Publishing doi:10.1088/1755-1315/1225/1/012044 2 cows [4], indicated the negative effect of heat stress when the temperature and humidity index rose above 72, and its effect on the productive performance of milk-producing cows [5]. An economic study indicated that stress caused economic losses in the United States estimated at $810 million annually [6] that bad environmental conditions during summer negatively affected to composition of cow's milk, as the milk contained a much lower percentage of fats, proteins, lactose and minerals [7] A study conducted by [8] revealed that the exposure of milk cows to heat stress reduced milk production by up to 17%. Also, a study conducted in China showed that the reason for the decrease in milk production is the cows' exposure to heat stress, especially during the months of June, July and August [9] As well as exposure to heat stress reduced cows' milk production from 17-53% and reduced feed intake by 48% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study conducted in China showed that the reason for the decrease in milk production is the cows' exposure to heat stress, especially during the months of June, July and August [9] As well as exposure to heat stress reduced cows' milk production from 17-53% and reduced feed intake by 48% [10]. Another study showed that the summer season had an effect on milk components where the percentage of fat was 3.71% and the protein percentage was 3.44%, compared to the winter season, which recorded 3.76% and 3.57%, respectively [7]. Therefore, well-coordinated efforts of all concerned bodies are required to enhance the productive performance of the cows [11].…”
Section: Introductionmentioning
confidence: 99%